2016
DOI: 10.1155/2016/1810327
|View full text |Cite
|
Sign up to set email alerts
|

“Inflammaging” as a Druggable Target: A Senescence‐Associated Secretory Phenotype—Centered View of Type 2 Diabetes

Abstract: Aging is a complex phenomenon driven by a variety of molecular alterations. A relevant feature of aging is chronic low-grade inflammation, termed “inflammaging.” In type 2 diabetes mellitus (T2DM), many elements of aging appear earlier or are overrepresented, including consistent inflammaging. T2DM patients have an increased death rate, associated with an incremented inflammatory score. The source of this inflammation is debated. Recently, the senescence-associated secretory phenotype (SASP) has been proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 127 publications
2
99
0
Order By: Relevance
“…The link between T2DM and inflammation is well established. T2DM is considered to be, in part, a consequence of subclinical chronic low-grade inflammation (1)(2)(3). Several studies have reported that circulating inflammatory cytokines, such as c-reactive protein, TNF-α, IL-1β, IL-6 and IL-18, are significantly elevated in T2DM patients (33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between T2DM and inflammation is well established. T2DM is considered to be, in part, a consequence of subclinical chronic low-grade inflammation (1)(2)(3). Several studies have reported that circulating inflammatory cytokines, such as c-reactive protein, TNF-α, IL-1β, IL-6 and IL-18, are significantly elevated in T2DM patients (33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) presents a major and growing health problem throughout the world. Microvascular and macrovascular complications often occur in T2DM, and chronic low-grade inflammation plays a central role in this process (1)(2)(3). The inflammatory response is associated with both insulin resistance and the development of vascular complications in T2DM patients (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The definite pathogenic relevance of senescence for the onset of type-2 diabetes and the progression of its multiorgan complications, or whether senescence precedes or follows the onset of perpetual inflammation and insulin resistance are topics of intense debate [7]. Anyhow, diabetic patients experience an obvious accelerated aging process that increases their predisposition to morbidity and earlier death.…”
Section: Diabetes Cellular Senesce and Chronic Woundsmentioning
confidence: 99%
“…As derived from a diabetic donor, this population of senescent, arrested cells may be impinged by a variety of hyperglycemia-associated stressor factors including reactive oxygen species. Different pathogenic loops linked to diabetes progression and complications development, appear to be mechanistically related to the orchestration of a senescencent phenotype [7].…”
Section: Introductionmentioning
confidence: 99%
“…Closely tied to the progression of clinical disease with advanced age are metabolic disorders (1, 10, 11, 41, 42) that includes DM (8, 43). In particular, DM is increasing in incidence throughout the world (28, 41) and it is predicted that greater than 350 million individuals currently have DM (4448).…”
Section: Increased Lifespan Degenerative Disorders and Cell Injurymentioning
confidence: 99%